AJARAN KESUSILAAN DALAM SATUA BALI MEN TIWAS TEKEN MEN SUGIH - Sanjaya Putu (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Satua is an educational medium that has existed in Bali since ancient times. Through satua, the values of education are conveyed by packaging stories that are interesting, educational, and teaching without patronizing. One of Bali's existing and popular units in Bali is the Satua Men Sugih signed by Men Tiwas. This Satua tells about two women who are very different in terms of the existence of life. Men Sugih was a rich woman but stingy, while Men Tiwas was a poor  and innocent woman. Satua Men  Sugih the Men Tiwas  signature contains the value  of moral education which, when linked to the teachings of Hinduism, actually teaches the listener to avoid mischief, and loba or greed. Besides that Satua Men Sugih signed by Men Tiwas mandated that good deeds would certainly be rewarded well, as well as the unrighteous deeds would get equal reward. Keywords: Bali Satua, Susila, Hinduism